Proceedings of International Ethical Hacking Conference 2018 eHaCON 2018, Kolkata, India - Chakraborty, Mohuya; Chakrabarti, Satyajit; Balas, Valentina Emilia; Mandal, J. K.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book discusses the implications of new technologies for a secured society. As such, it reflects the main focus of the International Conference on Ethical Hacking, eHaCon 2018, which is essentially in evaluating the security of computer systems using penetration testing techniques. Showcasing the most outstanding research papers presented at the conference, the book shares new findings on computer network attacks and defenses, commercial security solutions, and hands-on, real-world security experience. The respective sections include network security, ethical hacking, cryptography, digital forensics, cloud security, information security, mobile communications security, and cyber security.
Chapter 1.Social Engineering Attack Detection and Data Protection Model (SEADDPM) -- Chapter 2.OnlineKALI: Online Vulnerability Scanner -- Chapter 3.Towards an AI-Chatbot driven Advanced Digital Locker -- Chapter 4.A hybrid task scheduling algorithm for efficient task management in multi cloud environment -- Chapter 5.An Enhanced Post Migration Algorithm for Dynamic Load Balancing in Cloud Computing Environment -- Chapter 6.Cryptanalysis and Improvement of Three-Factor-Based Confidentiality-Preserving Remote User Authentication Scheme in Multi-server Environment -- Chapter 7.Bi-Symmetric Key Exchange: A Novel Cryptographic Key Exchanging Algorithm -- Chapter 8.DNA Cryptography Based Secured Weather Prediction Model in High Performance Computing -- Chapter 9.A Novel Approach of Image Steganography with Encoding and Location Selection -- Chapter 10.Image Encryption using Pseudorandom Permutation.-..etc.
Keywords: Telecommunication; Data protection; Data structures (Computer science).; Information theory; Communications Engineering, Networks; Data and Information Security; Data Structures and Information Theory